2009
DOI: 10.1111/j.1468-3083.2008.02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased carotid artery intima-media thickness and impaired endothelial function in psoriasis

Abstract: Background Psoriasis is associated with an increased risk of atherosclerosis. This study compared subclinical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
157
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 33 publications
25
157
2
9
Order By: Relevance
“…Recent studies revealed psoriasis as an independent risk factor for atherosclerosis, myocardial infarction, endothelial dysfunction, coronary artery disease, stroke and diabetes [3,10,22,23,24]. A recent study emphasized the comparable increase in major adverse CV events and CV deaths in patients with severe psoriasis and diabetes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed psoriasis as an independent risk factor for atherosclerosis, myocardial infarction, endothelial dysfunction, coronary artery disease, stroke and diabetes [3,10,22,23,24]. A recent study emphasized the comparable increase in major adverse CV events and CV deaths in patients with severe psoriasis and diabetes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction has been recognized as an early marker of subclinical atherosclerosis. FMD measurements are commonly used to evaluate endothelial function, and Balci et al [34] showed that psoriatic patients had lower FMD values than normal controls. Gonzalez-Juanatey et al [35] also demonstrated that the FMD percentage was lower in psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nos doentes psoriáticos, a EIM carotídea era maior nos indivíduos mais idosos, com doença mais prolongada e mais grave. Num estudo realizado por Baci et al 21 também se observou um aumento significativo da EIM das artérias carótida comum esquerda e direita nos doentes psoriáticos. O aumento na EIM carotídea dos doentes psoriáti-cos foi igualmente demonstrado por Arias-Santiago et al 22 A rigidez arterial é um preditor de eventos cardiovasculares adversos.…”
Section: Ateroscleroseunclassified